Memahami iklim motivasi dalam olahraga: Perspektif komparatif tentang atlet tim dan individu - Fatimah Azzahra, Syabani; Fitri, Mustika; Zaky, Mohammad; Apriady, Hilmy (Universitas Nusantara PGRI Kediri, 2025)
The motivational climate in sports is a crucial factor affecting athlete performance and well-being in both team and individual sports. This study compares the motivational climate between team and individual athletes. Using a quantitative descriptive method, the research involved 15 handball team athletes and 15 individual taekwondo athletes from West Java, selected through purposive sampling. All participants were female, aged 17 to 26 years, with a minimum of 3 years of competitive experience. Data were collected using the Perceived Motivational Climate in Sport Questionnaire (PMCSQ-2). Results showed that team athletes had a slightly higher motivational climate (M = 44.99, SD = 10.19) compared to individual athletes (M = 41.50, SD = 10.47). Team athletes also scored higher in ego and task orientations, with means of 44.23 and 45.74, respectively, while individual athletes scored 39.62 and 43.38. These findings suggest that team sports foster a more positive motivational climate due to stronger social support and group dynamics. Individual athletes focused more on skill mastery and personal goals, facing greater responsibility. This research provides insights for coaches and managers to improve the motivational climate in both team and individual sports, helping athletes achieve optimal performance and maintain mental health. Coaches should focus on individual athletes' personal achievements and support systems to enhance their well-being.